Empowering Families in Pediatric Tuberculosis Treatment: Enhancing Adherence through Education and Support - Agustin, Ismar; Azwaldi; Noviani, Inka; Febriani, Leha; Wulansari, Novia (Yayasan Rumah Ilmu Professor, 2025)
This research evaluates the effectiveness of a family empowerment program in improving medication adherence among children undergoing treatment for pulmonary tuberculosis (TB) in Desa Pangkalan Benteng, Indonesia. The study integrates qualitative and quantitative methods to assess the impact of a training program to increase family knowledge about TB and its treatment regimen. The results demonstrate a significant improvement in family knowledge and children's adherence to their treatment schedule after receiving education on medication management, side effect handling, and emotional support. The findings emphasize the critical role of family involvement in ensuring that children complete their treatment regimens and suggest that comprehensive family education programs can enhance treatment outcomes. The study highlights the potential of family-centered interventions in pediatric TB care and provides recommendations for expanding such programs to other chronic diseases.